The development strategy of Kazakhstan’s tax services (ҚазҰУ хабаршысы. Экономика сериясы, 2016)
The need for the formation of a new tax system came with the acquisitionof independence of Kazakhstan and the country’s transition to a marketeconomy. Market economy distinguishes competitiveness and self-regulation.Kazakhstan was the first CIS country has created progressive tax legislation.State adjusting tax policy provides country’s economic development. A moderntax system of Kazakhstan is aimed at the formation of the country’s centralfinancial resources and as close as possible to international. The tax system ofthe state must continuously improve and learn from the experience of moredeveloped countries. The main objective of the Strategic Development TaxService is the creation of high- tax service to the community satisfaction. Inmodern conditions the intensification of entrepreneurial activity, increasingfiscal literacy, one of the problems with the tax service is the quality of taxadministration. Modernization of tax service will have a positive impact on theadministrative burden elimination double existed in the form of duplicationof inspections, reporting forms, various levels of application of legislation andthe provision of public services. As a result, in the country, a new system ofinteraction between the state and business, this is aimed at creating favorableconditions for business development. And this, in turn, will attract new investorsto our country’s joining the 50 most developed countries of the world.